Teaching and learning Organic Chemistry in the view of High School teachers (Research, Society and Development, 2020)
Literature points out that the didactic model theory can be an artifice on establishing connections between thought, conceptions and beliefs of the teachers in their teaching practice. In this context, this article aims to verify the didactic models from a group of high school teachers in their approach of the curricular Organic Chemistry content and to search for evidence for how this discipline is being developed in this level of education. In order to obtain that, a questionnaire was adapted from literature and applied to 30 high school teachers from public and private network in Rio Grande do Sul. This instrument consists in 20 sentences that comprehend five didactic dimensions. The data analysis was made using the Statistical Package for Social Sciences (SPSS) software and the results show that the teachers’ Organic Chemistry teaching practice is guided by various didactic models, often antagonistic. Overall, in the context researched the Organic Chemistry approach targets to shape critic thinking citizens, it is related to the everyday life, it takes the students´ ideas and conceptions into consideration, it occurs through lecture classes and experimental verification activities, and lastly, it uses various evaluating instruments